Mangrove Diversity in Production Forest Management Unit (FMU) Bulungan Unit VIII North Kalimantan - Karlina Fitri Kartika; Istomo Istomo; Siti Amanah (Media Konservasi, 2018)
Mangrove ecosystem have various important roles as habitat for marine and terrestrial species. However, the ecosystem has recently faced anthropogenic threats delivered by the expansion of aquaculture pond. Study of mangrove diversity was conducted in Production FMU Bulungan Unit VIII, North Kalimantan. The study was aimed to analyze species diversity in the FMU Bulungan Unit VIII and determine community perception on existing mangrove condition. Vegetation analysis was applied to quantify mangrove community in two sampling locations, Salimbatu and Liagu, within 26 quadratic plots (10mx10m). As many as 63 respondents were interviewed to analyze communities’ perception. As the result, 10 species were identified species and one unidentified species recorded during the survey. Rhizophoraceae was dominated the species composition in sampling area. Rhizophora mucronata had the highest Importance Value Index in tree and seedling stage while Rhizophora apiculata was dominant in sapling stage. On the other hand, Bruguiera parviflora was recorded on each growth stages in all sampling plots. Species diversity index (H’) of mangrove vegetation in the FMU was found at 1,68 with species richness index value 1,58. This diversity index considered as moderate diverse since only few vegetation species are able to live in the mangal. The perpendicular structure of mangrove in the FMU formed an inverse J-shape which showed normal growth of uneven-age forest stand. The interview result implied that more than 50% of the respondent considered that mangrove condition in their village area has been disturbed. Therefore mangrove management with local community involvement is neccessarily required to improve the mangrove performance. Keywords: communities perception, habitat, mangrove, species diversity